HUBUNGAN KEPERCAYAAN DIRI SISWA DENGAN HASIL BELAJAR MATEMATIKA BILANGAN BULAT PADA SISWA KELAS 4B DI SD BANI SALEH 01 BEKASI - Hasanah, Nur; Kamili, Luthfiah; Mareta, Seli (El Banar : Jurnal Pendidikan dan Pengajaran, 2024)
This research was conducted to obtain empirical data about the relationship between self-confidence and integer mathematics learning outcomes. The research was conducted using a quantitative approach with relational and survey techniques. The sample for this research was 30 students who were active in the 2023/2024 academic year obtained through random sampling techniques. Data uses descriptive analysis and inferential analysis. The research results show that there is a positive correlation between self-confidence (variable X) and mathematics learning outcomes (variable Y). This is proven by the correlation coefficient (r)=0.956 with the regression equation Ŷ=13.107+0.088X. The coefficient of determination shows that r2=(0.956)2×100%=91.3%. This means that students' mathematics learning outcomes are influenced by their self-confidence. So this research concludes that there is a positive relationship between self-confidence and students' mathematics learning outcomes. Key words: mathematics learning outcomes, relationships, self-confidence.